2018
DOI: 10.12944/crnfsj.6.2.27
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Mineral Retention and Anti-Nutritional Compounds Degradation During Bean Cooking Process

Abstract: The objective of this study was to determine the effect of soaking, boiling and frying on retention of micro-minerals as well as degradation of polyphenols and phytic acids. Soaking of the beans did not significantly (p > 0.05) decrease mineral, total polyphenol and phytic acid content of beans. While boiling of beans significantly (p < 0.05) decreased the concentration of total polyphenols and phytic acid but not the mineral content of the beans. Frying of boiled beans decreased the total polyphenol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…To our knowledge, no other studies have reported iron retention after refrying beans. Values > 100% for AR as reported in our study were also reported before by Ongol et al [36] and Ferreira et al [35]. The high AR of > 100% for iron retention can possibly be explained by the leakage of solubles in the water (10.1-20.5%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, no other studies have reported iron retention after refrying beans. Values > 100% for AR as reported in our study were also reported before by Ongol et al [36] and Ferreira et al [35]. The high AR of > 100% for iron retention can possibly be explained by the leakage of solubles in the water (10.1-20.5%).…”
Section: Discussionsupporting
confidence: 90%
“…Micronutrient losses during food processing and cooking can be measured by determining True Retention (TR), where the changes in solids of food during processing and cooking are taken into account, to provide an accurate estimation of actual retention during the different processes [32]. Retention studies that have tested conventional [34][35][36] and biofortified beans [32] have been published. However, the studies to date have not reported TR, which makes it difficult comparing results across different studies.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the high phytate-to-Fe molar ratios given in Table 2, it can be suggested that Fe present in all barley populations is not bioavailable. Similarly, this result is in line with the findings of Ongol et al [41] and Hummel et al [42]. Hence, the bioavailability of iron of most barley populations (95.4%) was inhibited.…”
Section: Mineral Element Concentrations In Barley Populationssupporting
confidence: 91%
“…Fermented white bean homogenate is likely to contribute natural antioxidants like polyphenols (e.g., flavonoids, phenolic acid) and proteins (e.g., albumins, globulins, and phaseolin) [49][50][51][52]. Processes like soaking, sprouting, and fermentation can influence the polyphenol content of white beans, with fermentation potentially converting complex polyphenols into simpler, more bioavailable forms [9,10]. Studies on other legumes, such as soybeans, suggest that fermentation can influence enzymatic activities and potentially affect polyphenol content [53].…”
Section: Abtsmentioning
confidence: 99%
“…White kidney beans are particularly rich in polyphenols, offering a spectrum of health benefits such as antioxidant, antidiabetic, antiobesity, antiinflammatory, antimutagenic, and anticarcinogenic properties [8]. Fermentation, an age-old process, further unlocks the potential of these bioactive compounds by enhancing their bioavailability, thereby potentially amplifying their health-promoting effects [9,10]. By introducing specific microbial strains, fermentation can enhance the bioavailability of bioactive compounds within white kidney beans, unlocking greater health benefits.…”
Section: Introductionmentioning
confidence: 99%